GROWTH AND YIELDING OF FROSTBITTEN PEACH TREES AFTER REGENERATIVE PRUNING - Bożena Radajewska; Michał Szklarz (Acta Scientiarum Polonorum: Hortorum Cultus, 2009)
In the years 2006–2008 in Przybroda near Poznań the objects of studies were peach trees ‘Harbinger’ on rootstocks Manchurian Peach, Sand Cherry and Rakoniewicka Seedling, formed as a spindle, severely damaged by frost in 2005/2006 winter. In May 2006, an intensive tree pruning was carried out. The objective of studies included the estimation of the pruning effect and rootstocks of frostbitten trees on the process of their regeneration and yielding. Pruning caused a decrease of tree height and crown width in relation to control. Trunks of the strongly pruned trees became thicker, as compared with control trees. In the third year after regenerative pruning, the trees decreased their yield by about 30% in relation to control. The best yielding trees were on rootstock Rakoniewicka Seedling, but the weakest on Sand Cherry.